Peran UMKM di Kota Depok dalam Pembangunan Ekonomi Berkelanjutan dan Kesejahteraan Masyarakat pada Provinsi Jawa Barat - Ester Veronika; Innaya Izti; Chika Yunita; Nabila Pebriyani; Dzannuba Dirgantara (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to identify the strategic role of MSMEs in driving sustainable economic growth in Depok City and its impact on improving community welfare in West Java. Through qualitative and quantitative approaches, this study analyzes various factors that influence MSME performance. The results of the study are expected to provide effective policy recommendations to support the development of MSMEs in Depok City.